CH4 and N2O Emissions From Cattle Excreta: A Review of Main Drivers and Mitigation Strategies in Grazing Systems - Rivera, Julián Esteban; Chará, Julian (Frontiers in Sustainable Food Systems, 2021)
Cattle production systems are an important source of greenhouse gases (GHG) emitted to the atmosphere. Animal manure and managed soils are the most important sources of emissions from livestock after enteric methane. It is estimated that the N2O and CH4 produced in grasslands and manure management systems can contribute up to 25% of the emissions generated at the farm level, and therefore it is important to identify strategies to reduce the fluxes of these gases, especially in grazing systems where mitigation strategies have received less attention. This review describes the main factors that affect the emission of GHG from manure in bovine systems and the main strategies for their mitigation with emphasis on grazing production systems. The emissions of N2O and CH4 are highly variable and depend on multiple factors, which makes it difficult to use strategies that mitigate both gases simultaneously. We found that strategies such as the optimization of the diet, the implementation of silvopastoral systems and other practices with the capacity to improve soil quality and cover, and the use of nitrogen fixing plants are among the practices with more potential to reduce emissions from manure and at the same time contribute to increase carbon capture and improve food production. These strategies can be implemented to reduce the emissions of both gases and, depending on the method used and the production system, the reductions can reach up to 50% of CH4 or N2O emissions from manure according to different studies. However, many research gaps should be addressed in order to obtain such reductions at a larger scale.